Structurally controlled cell growth on modified polymer surfaces - Kvítek, Ondřej; Smejkalová, Zuzana; Peterková, Lucie; Rimpelová, Silvie; Řezníčková, Alena; Švorčík, Václav (Vacuum, 2019)
Cells are subject to various stimuli in their natural environment, which substrates for their culturing should be aspiring to imitate, because it is necessary for their correct function. Substrate topography is one of the stimuli as the cells in vivo are directed to only grow according to the extracellular matrix. In this work, we explored methods of microstructured modification of polymer substrates using masked cathode sputtering of Au and plasma etching to produce materials with contrasting cytocompatibility surface microstructure. Au was sputtered on poly-l-lactic acid through a metal mask. The microstructure was successfully prepared on the sample surface, but growth of the mouse fibroblast cells (L929) used for the cytocompatibility study did not respect features of the prepared material. Polytetrafluoroethylene was exposed to plasma treatment, which leads to the ablation of the surface polymer layer causing changes of its surface morphology and chemistry and improves its cytocompatibility. The cell growth was following the prepared microstructure in this case, but the experiment was found to be strongly dependent on the parameters of the cell cultivation, because with longer cultivation times the prepared structure was covered with a great amount of the growing cells. •Polymer substrates were microstructurally modified using laser cut metal masks.•Plasma treated PTFE has increased wettability and surface roughness.•PLLA with sputtered Au layer showed insufficient cytocompatibility contrast.•No material of the masks was found by XPS on the samples after the treatment process.•Modified PTFE showed controlled growth of L929 cells according to the modification.